2019
DOI: 10.1016/j.bioactmat.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Powder metallurgical Ti-Mg metal-metal composites facilitate osteoconduction and osseointegration for orthopedic application

Abstract: In this work, Ti—Mg metal-metal composites (MMCs) were successfully fabricated by spark plasma sintering (SPS). In vitro, the proliferation and differentiation of SaOS-2 cells in response to Ti—Mg metal-metal composites (MMCs) were investigated. In vivo, a rat model with femur condyle defect was employed, and Ti—Mg MMCs implants were embedded into the femur condyles. Results showed that Ti—Mg MMCs exhibited enhanced cytocompatibility to SaOS-2 cells than pure Ti. The micro-computed tomography (Micro-CT) result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…As orthopedic and spinal implants for PAEK, concerns raised regarding the new bone formation and osseointegration, which has been one of the critical issues for long-term success rates of orthopedic implants [ 13 ]. Good osteointegration performance is necessary for a permanent orthopedic device, because the osteointegration will directly impact the initial and long-term stability of the implant [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As orthopedic and spinal implants for PAEK, concerns raised regarding the new bone formation and osseointegration, which has been one of the critical issues for long-term success rates of orthopedic implants [ 13 ]. Good osteointegration performance is necessary for a permanent orthopedic device, because the osteointegration will directly impact the initial and long-term stability of the implant [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mg is also biodegradable, and thus, this composite is ideal for orthopedic implants. Not only does its addition adjust pure titanium's properties to approach that of bone but it also allows for Mg degradation over time with the resulting structure having good osteointegration [73][74][75][76][77]. Thus, the increased corrosion rate of the Ti + Mg composite is advantageous for such applications.…”
Section: Titaniummentioning
confidence: 99%
“…Titanium added to iron, aluminium, vanadium, molybdenum, tantalum and other metals forms lightweight and strong alloys, commonly used in aerospace (jet engines, spacecraft and missiles), metallurgy processes, dental/medical applications (prostheses, orthopedic implants, dental and endodontic instruments and files, dental implants), the car industry, agriculture, the military, sporting goods, mobile phones, jewellery and other applications [3][4][5], as shown in Figure 1. For example, Ouyang et al, (2019) have shown that Ti-Mg metal-metal composites facilitate osteoconduction and osseointegration (significantly higher around Ti-Mg than that around Ti implants) for orthopedic application [6]. Similarly, increased osseointegration has been observed on Ti 35 Zr 28 Nb alloy than that on pure titanium [7].…”
Section: Introductionmentioning
confidence: 99%